Magnetic materials in Japan : research, applications, and potential (Elsevier materials technology in Japan series., 1991)
Please note this is a Short Discount publication. This, the third report in Elsevier's Materials Technology in Japan series, concentrates on magnetic materials as a topic gaining worldwide attention, and each chapter looks not only at current research, but also describes the technology as it is being applied and its future potential. Magnetic-related research is the second largest field of research in Japan after semiconductors, with the estimated number of researchers and engineers engaged in magnetics-related activities currently at 20,000. This research report serves as both a review of research undertaken and developments to date, and a forecast of where the industry is going.